Shift or Maintenance? A Sociolinguistic Study of the Tetun Language amidst the Dynamics of Language Policy in Timor-Leste - Anuno, Agustinho Da Conceicao (Journal of Language, Education, Literature, and Culture, 2025)
This study examines the dynamics of language shift and maintenance in Timor-Leste, focusing on the Tetun language. Tetun, as the co-official language alongside Portuguese, plays a key role in national identity and daily communication. However, challenges arise due to globalization, educational reforms, and the growing influence of Portuguese and English, especially among youth and in formal domains such as schools and public administration. Despite its official status, Tetun's vitality is increasingly questioned. This study aims to investigate how language policies, societal attitudes, and institutional practices affect the use and transmission of Tetun across generations. Using a mixed-methods approach, this study combines qualitative and quantitative data from surveys, interviews, and observations in educational and community contexts. Findings show that while Tetun remains strong in informal settings, it faces marginalization in formal domains due to the dominance of Portuguese and insufficient institutional support. The results highlight a mismatch between policy recognition and practical implementation. This study concludes that effective language maintenance requires culturally rooted and community-driven strategies. It contributes to the broader understanding of language policy in post-colonial multilingual societies and provides practical insights for sustaining indigenous languages like Tetun amid shifting sociolinguistic conditions